ICT-Driven Smart HRM in Hospitals: A Scopus-Based Bibliometric Analysis of Trends and Themes - Susi Indrawati; Qurratul Aini (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The advancement of digital technologies such as artificial intelligence, big data analytics, and cloud computing has significantly transformed Human Resource Management (HRM) practices in hospitals. This transformation aims to enhance operational efficiency, service quality, and employee well-being. However, this study explores global trends by analyzing the impacts, challenges, and opportunities of HRM digitalization in hospital settings. Technology adoption also presents challenges, including digital stress, data privacy concerns, and organizational readiness. A qualitative bibliometric analysis was conducted using VOS viewer software. A total of 131 articles were published between 2019 and 2024, indexed in the Scopus database. The findings reveal five key themes: operational efficiency, decision support systems, employee engagement, adaptive leadership, and knowledge management. India, China, and Malaysia are the top contributing countries in this research domain. Nonetheless, challenges such as infrastructure readiness, workforce training, and psychosocial impacts of digitalization remain prominent. ICT integration in hospital HRM holds great potential in supporting healthcare transformation by enhancing efficiency, training, and data-driven performance evaluation. However, a balanced digitalization strategy is needed, one that considers employee well-being and ethical concerns. Future research should further explore the role of leadership in digital change and develop sustainable frameworks to support technology-based HRM.